2022
DOI: 10.3390/nu14091900
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Before, during and after Pregnancy: Effect on Neonates and Children

Abstract: A worldwide high prevalence of vitamin D (VD) deficiency has become of growing concern because of potential adverse effects on human health, including pregnant women and their offsprings. Beyond its classical function as a regulator of calcium and phosphate metabolism, together with its fundamental role in bone health in every stage of life, its deficiency has been associated to multiple adverse health effects. The classic effects of VD deficiency in pregnancy and neonates have been late hypocalcemia and nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 152 publications
1
56
0
7
Order By: Relevance
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested links among plasma vitamin D levels and preterm birth or other pregnancy-related outcomes including pre-eclampsia, polycystic ovary syndrome, and endometriosis 18,19 . Vitamin D deficiency was found associated with many adverse outcomes including those related to pregnancy, whereas increased levels of the protein product of GC showed association with a reduced risk of certain immune-mediated diseases 19,31,32 . The precise role of GC in the context of human pregnancy and SPTB remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the classification standard for the determination of serum 25(OH)D concentration recommended by the IOM is still an indicator commonly used internationally to categorize the vitamin D status in adults. A large number of studies [6,11,25,26] published in recent years emphasize the relationship between low vitamin D status and several adverse pregnancy outcomes such as PE, GDM, preterm birth, etc according to IOM standard. Rostami et al [27] infer the ideal level of vitamin D during pregnancy based on pregnancy outcomes, they recommend a cutoff of 25(OH)D >37.5 nmol/L for the prevention of adverse pregnancy outcomes.…”
Section: 【 【 【Discussion】 】 】mentioning
confidence: 99%